Exploring the Meaning of Silence in the Japanese and English versions of Castle in the Sky (1986) - Ami, Eriko (fi=Turun yliopisto|en=University of Turku|, 2018)
This thesis explores the meaning of silence in Hayao Miyazaki’s Castle in the Sky (1986). Silence, in the original Japanese film, plays an important role in the overall soundscape. However, the film’s two English versions produced by Buena Vista, a former branch of the Walt Disney Company, fill quiet moments with additional music and dialogue. Notably, Japanese and American animation have different traditions in terms of soundscapes and target age. Japanese animation often features silence as it depicts scenes in realistic ways. These animations target a certain age group (children, boys, girls, men, or women), yet attract a wide range of audiences with complex themes and narratives. Meanwhile, American animation, especially those that Disney produces, are generally musicals geared towards children. The music in these productions tends to dominate the soundscapes of Disney films to catch and maintain the attention of the young audience. This research investigates whether the filled silence in the two English versions (the Disney dubbed version [2003] and the Remixed version [2010]) change or keep the meanings of silence in the original, from the point of view of audiovisual translation. Moreover, the study seeks to quantify the amount of silence in the Japanese and English versions of the film. Thereafter, this study examines how each English version fills the silent moments in the original. In addition, the study seeks to analyze meanings connected to silence in each version. To answer these questions, this study employs two methodologies: content analysis and semiotic analysis. First, the content analysis sets two definitions of silence: prolonged silence and non-verbal communication between the characters. The results of the analysis show that the Japanese version has 60 silences that match the first definition and 87 silences for the second definition. As for the English versions, the Disney dubbed version (2003) fills 78% of prolonged silence and 68% of non-verbal communication with music. The Remixed version (2010) fills 68% of prolonged silence and 53% of non-verbal communication. These results are discussed and explored in this study. Second, the semiotic analysis interprets the meaning of 15 selected silences from the results of the content analysis. Most of these silences indicate that filled silence translates realism into fantasy so that the meanings are accessible to the American audience and the English version fits its target audience. I conclude that the phenomenon of the filled silence aims to bridge the different systems of representation in Japan and the United States as well as accommodate the different target ages of the Japanese and the English versions.